A mittenwaldi oltárképtől a „Máté-passióig”. Teológiai implikációk Paul Gerhardt „Ó, Krisztusfő, te zúzott” énekében - Krisztián KOVÁCS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2018)
From the Altar-piece from Mittenwalde to the Matthew-Passion: Theological implication in Paul Gerdhardt’s hymn „O, Sacred Head, Now Wounded”.